Behavioural analysis of postnatal physical activity in the UK according to the COM-B model: a multi-methods study. Issue 8 (2nd August 2019) - Ellis, Kate; Pears, Sally; Sutton, Stephen
Abstract : Objective: Develop a behavioural analysis of factors influencing postnatal physical activity (PA) according to the 'capability, opportunity, motivation and behaviour' (COM-B) model of behaviour to inform intervention development using the Behaviour Change Wheel (BCW). Design: Cross-sectional, multi-method study using semi-structured interviews and a quantitative questionnaire. Setting: Children's centres and mother and baby groups in Hertfordshire and Cambridgeshire, UK. Participants: Convenience samples of postnatal women were interviewed (n=16) and completed the questionnaire (n=158). Methods: Semi-structured interviews followed a preprepared topic guide exploring the COM-B model components and analysed using framework analysis. The questionnaire, based on the self-evaluation of behaviour questionnaire, was adapted using patient and public involvement and findings from the interviews. Questionnaire participants rated their agreement with 22 predefined statements related to COM-B model components. Mean, SD and 95% CI were calculated and each item categorised according to importance. Demographic data were collected. Results: The questionnaire identified that new mothers would be more active if they had more time, felt less tired, had accessible childcare, were part of a group, advised by a healthcare professional, able to develop a habit and had more motivation. Additional themes emerging from qualitative data were engaging in PA groups with other new mothers, limited physical stamina following complicated births, social interaction, enjoyment and parental beliefs as motivation, provision of child-friendly PA facilities and environments and babies' unpredictable routines. Conclusion: The behavioural analysis presented in this paper identifies and adds detail on the range of factors influencing the target behaviour. Some are unique to the target population, requiring targeted interventions for postnatal women, whereas some are individualised, suggesting the need for individually tailored interventions. We will use the behavioural analysis presented to design an intervention using the subsequent steps in the BCW.